Chloracne: a case series on cutaneous expression of CYP1A1 as diagnostic biomarker. (1st July 2021) - Chessa, M. A.; La Placa, M.; Patrizi, A.; Virdi, A.; Misciali, C.; Fedrizzi, G.; Filippi, F.; Saurat, J.‐H.; Sorg, O.; Fontao, F.; Kaya, G.; Neri, I.
Summary: Chloracne, also known as metabolizing acquired dioxin‐induced skin hamartomas (MADISH), is a rare disfiguring disease related to dioxin exposure. There is a paucity of literature on the clinical manifestations and pathogenesis of chloracne/MADISH. The aim of this study was to assess the clinical features of this very unusual acneiform eruption and to explore the pathogenesis of the disease. This was a retrospective, observational report study was conducted on five patients belonging to the same nuclear family (father, mother and three children) and a relative (father's brother) living in the same house. Histopathological, immunohistochemical, laboratory and toxicological analyses were performed for all patients. The results suggest that CYP1A1 in human skin is a diagnostic biomarker in chloracne, and was positive for all the patients in our sample. Tetrachlorodibenzo‐ p ‐dioxin is the most investigated dioxin responsible for chloracne; however, several other agonists, whether dioxin‐like or not, can activate the aryl hydrocarbon receptor. To our knowledge, this Italian case series is the first study to suggest polychlorinated biphenyls as a possible cause of an overstimulation of aryl hydrocarbons causing the consequent acneiform eruption.